2012
DOI: 10.1093/nar/gks705
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs associated with the different human Argonaute proteins

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that function in literally all cellular processes. miRNAs interact with Argonaute (Ago) proteins and guide them to specific target sites located in the 3′-untranslated region (3′-UTR) of target mRNAs leading to translational repression and deadenylation-induced mRNA degradation. Most miRNAs are processed from hairpin-structured precursors by the consecutive action of the RNase III enzymes Drosha and Dicer. However, processing of miR-451 is Dicer independent and cleav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
166
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(180 citation statements)
references
References 52 publications
11
166
0
1
Order By: Relevance
“…Because, in mammals, only Ago2 is catalytically active and needed for efficient gene knockdown, noncatalytical Ago1, Ago3, and Ago4, however, may cause unwanted off-target effects. Thus, a miR-451-like hairpin could be used for siRNA or ectopic miRNA expression to minimize the off-target effects (7,10,31,33). To our disappointment, processing as well as silencing activity was less efficient compared with classical, Dicer-dependent hairpins (33).…”
Section: Mechanisms Of Mir-451 Biogenesismentioning
confidence: 93%
See 1 more Smart Citation
“…Because, in mammals, only Ago2 is catalytically active and needed for efficient gene knockdown, noncatalytical Ago1, Ago3, and Ago4, however, may cause unwanted off-target effects. Thus, a miR-451-like hairpin could be used for siRNA or ectopic miRNA expression to minimize the off-target effects (7,10,31,33). To our disappointment, processing as well as silencing activity was less efficient compared with classical, Dicer-dependent hairpins (33).…”
Section: Mechanisms Of Mir-451 Biogenesismentioning
confidence: 93%
“…Recently, Yang and colleagues show that the degree of G:C content in the resected region governs the maturation efficiency of 3 0 resection and resultant regulatory activity, such that a relatively low G:C content improves processing (31). Furthermore, Dueck and colleagues reported that miR-451 is not only processed by Ago2, but also loaded exclusively into Ago2-containing RISCs (33). In RNA interference (RNAi), that siRNAs are loaded into all 4 Ago proteins.…”
Section: Mechanisms Of Mir-451 Biogenesismentioning
confidence: 99%
“…Genomic approaches have shown that some miRNA subpopulations preferentially bind to a certain argonaute protein (Ago1, Ago3, Ago4 -which might be redundant-and Ago2) in a context dependent manner with different implications in carcinogenesis. 134,27 Conversely, miRNA incorporation to the RISC complex might be regulated and influenced by different factors; one of them is incorporation of ago 3, which enhances the incorporation of the passenger strand of the tumor suppressor let-7a (let7-a*) to the RISC complex, and by consequence, promotes its biological activity in cancer cells. It seems that Ago3 modulates the ratio between microRNA guide and passenger strands.…”
Section: Argonaute a Multi-role Protein In Cancermentioning
confidence: 99%
“…201,202 This lack of Dicer recognition is due to the too-short base-paired duplex. 203,204 Surprisingly, this class of miRNA is not destroyed but processed by other nucleases and is shown to be active in the RNAi pathway. In fact, the Ago2 enzyme as part of the RISC complex processes these short duplexes to activate the mature miRNA strand.…”
Section: Discussionmentioning
confidence: 99%